2018
DOI: 10.3389/fnagi.2018.00215
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Functional Connectivity Density in Amyotrophic Lateral Sclerosis

Abstract: Purpose: Amyotrophic lateral sclerosis (ALS) is a motor neuro-degenerative disorder that also damages extra-motor neural pathways. A significant proportion of existing evidence describe alterations in the strengths of functional connectivity, whereas the changes in the density of these functional connections have not been explored. Therefore, our study seeks to identify ALS-induced alternations in the resting-state functional connectivity density (FCD).Methods: Two groups comprising of 38 ALS patients and 35 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 96 publications
(142 reference statements)
6
32
0
Order By: Relevance
“…These results were consistent with previous studies reporting decreased interhemispheric FC of the primary motor cortex (Fang et al, 2016;Zhang et al, 2017), and were supported by the findings of decreased degree centrality and FC density in the primary motor cortex in patients with ALS (Li et al, 2018;Zhou et al, 2016). Likewise, the ROI-based FC analysis also showed a lower FC between the precentral ROI and the right cerebellar ROI in patients with ALS.…”
Section: Fc Alterations In Alssupporting
confidence: 92%
See 1 more Smart Citation
“…These results were consistent with previous studies reporting decreased interhemispheric FC of the primary motor cortex (Fang et al, 2016;Zhang et al, 2017), and were supported by the findings of decreased degree centrality and FC density in the primary motor cortex in patients with ALS (Li et al, 2018;Zhou et al, 2016). Likewise, the ROI-based FC analysis also showed a lower FC between the precentral ROI and the right cerebellar ROI in patients with ALS.…”
Section: Fc Alterations In Alssupporting
confidence: 92%
“…Likewise, the ROI-based FC analysis also showed a lower FC between the precentral ROI and the right cerebellar ROI in patients with ALS. These results were consistent with previous studies reporting decreased interhemispheric FC of the primary motor cortex (Fang et al, 2016;Zhang et al, 2017), and were supported by the findings of decreased degree centrality and FC density in the primary motor cortex in patients with ALS (Li et al, 2018;Zhou et al, 2016). Notably, however, there also existed some fMRI studies showing increased FC or activation of the primary motor cortex in patients with ALS Menke et al, 2016).…”
Section: Fc Alterations In Alssupporting
confidence: 92%
“…Abnormal functional connectivity has been demonstrated in patients with ALS. Li et al demonstrated that patients with ALS were found to have decreased resting state short‐range functional connectivity density in the primary motor cortex and increased long‐range functional connectivity density in the premotor cortex. Impaired motor cortical subnetwork with reduced white matter connectivity was also detected in ALS and became more prominent over time .…”
Section: Discussionmentioning
confidence: 99%
“…The brain areas with static ALFF differences in patients with ALS are consistent with previous reports (Luo et al 2012;Ma et al 2016), except that the right inferior temporal gyrus had increased ALFF. The temporal lobe with aberrant activation and connection in patients with ALS was discovered in preceding rs-fMRI articles (Li et al 2018b;Loewe et al 2017;Zhou et al 2016). Besides, the thinning of cerebral cortex in the right inferior temporal gyrus is related to rapid clinical progression in ALS (Verstraete et al 2012).…”
Section: Alterations In Static Alffmentioning
confidence: 99%
“…Dysfunction of the right lingual gyrus in ALS was documented, including metabolic difference (Verma et al 2013) and functional connectivity (Li et al 2018b). The lingual gyrus is an important area in the visual system (Yang et al 2015), and 24.13% of Chinese ALS population are considered with visuospatial disability (Wei et al 2015).…”
Section: Alterations In D-alffmentioning
confidence: 99%